Inkjet‐printed antennas, sensors and circuits on paper substrate. Issue 10 (1st July 2013) - Kim, Sangkil; Cook, Benjamin; Le, Taoran; Cooper, James; Lee, Hoseon; Lakafosis, Vasileios; Vyas, Rushi; Moro, Riccardo; Bozzi, Maurizio; Georgiadis, Apostolos; Collado, Ana; Tentzeris, Manos M.
Abstract : Inkjet‐printing is a very promising technology for the development of microwave circuits and components. Inkjet‐printing technology of conductive silver nanoparticles on an organic flexible paper substrate is introduced in this study. The paper substrate is characterised using the T‐resonator method. A variety of microwave passive and active devices, as well as complete circuits inkjet‐printed on paper substrates are introduced. This work includes inkjet‐printed artificial magnetic conductor structures, a substrate integrated waveguide, solar‐powered beacon oscillator for wireless power transfer and localisation, energy harvesting circuits and nanocarbon‐based gas‐sensing materials such as carbon nanotubes and graphene. This study presents an overview of recent advances of inkjet‐printed electronics on paper substrate.